Women and men’s psychological adjustment after abortion: a six months prospective pilot study - Canário, Catarina (2011)
Background: The psychological impact of abortion is a controversial issue. While some studies indicate that women who had elective abortions present lower psychological distress when compared with those who had spontaneous or therapeutic abortions, other studies found abortion to be associated with significant psychological distress. Objectives: To assess psychological adjustment (emotional disorder, trauma symptoms and couple relationship) one and six months after abortion, and gender differences regarding psychological adjustment, and to assess the moderation role of couple relationship in the effect of the etiology of abortion on emotional disorder and trauma symptoms. Methods: Women (n=50) with different etiologies of abortion agreed to participate, as well as 15 partners (N=65). Assessments took place one and six months after abortion. Measures included the Brief Symptoms Inventory, the Impact of Event Scale-Revised and the Relationship Questionnaire. Results: A decrease in emotional disorder for all etiologies of abortion and an increase in perceived quality of couple relationship in therapeutic abortion were observed over time. Couple relationship moderates the effect of the etiology of abortion on trauma symptoms one month after abortion. Conclusion: Psychological adjustment after abortion seems not to be exclusively related to its etiology, being influenced by other factors such as couple relationship.